The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1002/ajmg.1320570339
|View full text |Cite
|
Sign up to set email alerts
|

Velo‐cardio‐facial syndrome: Frequency and extent of 22q1l deletions

Abstract: Velo-cardio-facial (VCFS) or Shprintzen syndrome is associated with deletions in a region of chromosome 22q11.2 also deleted in DiGeorge anomaly and some forms of congenital heart disease. Due to the variability of phenotype, the evaluation of the incidence of deletions has been hampered by uncertainty of diagnosis. In this study, 54 patients were diagnosed with VCFS by a single group of clinicians using homogeneous clinical criteria independent of the deletion status. Cell lines of these patients were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 17 publications
8
111
0
2
Order By: Relevance
“…Our results showed that the majority of the 44 adults with 22q11DS studied shared a common 3.1 Mb hemizygous deletion of 22q11.2, consistent with the literature (Carlson et al 1997;Kurahashi et al 1997;Lindsay et al 1995;Saitta et al 2004). We refined the proximal breakpoint location to a ~250 Kb segment between USP18 and PRODH, and the distal breakpoint to a ~350 Kb segment between D22S936 and HIC2.…”
Section: Common Deletion Variants and Recurrent Breakpoint Regionssupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that the majority of the 44 adults with 22q11DS studied shared a common 3.1 Mb hemizygous deletion of 22q11.2, consistent with the literature (Carlson et al 1997;Kurahashi et al 1997;Lindsay et al 1995;Saitta et al 2004). We refined the proximal breakpoint location to a ~250 Kb segment between USP18 and PRODH, and the distal breakpoint to a ~350 Kb segment between D22S936 and HIC2.…”
Section: Common Deletion Variants and Recurrent Breakpoint Regionssupporting
confidence: 92%
“…1), with the exception of the short nested 1.4 Mb deletion (ID 24), which had a distal breakpoint in a ~100 Kb segment between ARVCF and RANBP1. This deletion appears similar to the 1.5 Mb deletion previously described (Carlson et al 1997;Kurahashi et al 1997;Lindsay et al 1995;Saitta et al 2004), with breakpoints between D22S933 and ZNF74 (~706 Kb). The distal deletion breakpoint of these proximal nested deletions is commonly believed to be in LCR-B (Saitta et al 2004), although this would not appear to be the case for the 1.4 Mb deletion we found (Fig.…”
Section: Common Deletion Variants and Recurrent Breakpoint Regionssupporting
confidence: 82%
See 1 more Smart Citation
“…Among them was the anonymous genomic sequence D22S1660, which was derived from cosmid sc11.1. FISH experiments using this cosmid as a probe demonstrated that the region was duplicated on 22q11 and deleted in most patients with VCFS/DGS Lindsay et al 1993Lindsay et al , 1995. We determined that the duplicated region was demarcated by the markers 444P24Sp6 and D22S1660 and included the genes for DGCR6 and PRODH (proline dehydrogenase) ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The FISH mapping revealed that two loci were present on 22q11, named sc11.1a (centromeric) and sc11.1b (telomeric), and were situated 1-2 Mb apart . Both loci were shown to be deleted in VCFS/DGS patients with the 3 Mb and 1.5 Mb deletions and therefore in most patients with VCFS/DGS (Lindsay et al , 1995.…”
mentioning
confidence: 97%